A method for preparing multi-stage nanofiber composite membrane for membrane distillation
Through electrospinning technology, PVDF-HFP and TPU are blended with spinning wire, and longitudinal hydrophilic components are introduced to modify membrane pores, solving the problems of low permeability flux of traditional membrane distillation and easy wetting of membrane pores, achieving efficient and stable membrane distillation performance, and having wide industrial application potential.
Patent Information
- Application Number
- CN202210780721.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-07-05
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2042-07-05
AI Technical Summary
The penetration flux of the membrane for traditional membrane distillation and the membrane pores are easy to wet, resulting in poor interception effect, limiting the large-scale industrial application of membrane distillation technology.
Polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP) and thermoplastic polyurethane (TPU) are blended with wire through electrospinning technology, and longitudinal hydrophilic components are introduced to modify the membrane pores to improve the permeability flux of the hydrophobic porous membrane.
The membrane with high pores, high permeability, high hydrophobicity and excellent mechanical properties has been achieved, which significantly improves the efficiency and stability of membrane distillation, and has broad application prospects in the fields of seawater desalination and bitter and brackish water purification.
Smart Images

Figure CN115463554B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of membrane distillation system application, and specifically relates to a preparation method for a nanofiber membrane for hydrophobic porous membrane distillation by modifying membrane pores with longitudinal hydrophilic components to improve the flux. Background Art
[0002] Membrane distillation (MD) is a non-isothermal membrane separation technology that uses a hydrophobic porous membrane as a separation unit and the vapor pressure gradient between the hot feed side and the cold permeate side as a driving force to achieve separation and purification of mixed liquids. Compared with other membrane separation processes, the MD process has unique advantages, such as theoretically 100% retention of non-volatile molecules, lower operating temperature and pressure, and the ability to treat high-salt wastewater. Due to these advantages, MD is expected to become an alternative solution for seawater desalination, brackish water treatment, and the removal of organic and heavy metals in aqueous solutions. However, in the preparation of traditional MD membranes, it is difficult to balance the permeate flux and the retention rate, which restrict each other, reduce the separation efficiency, and limit its large-scale commercial application.
[0003] According to the characteristics of membrane distillation system, the first function of the membrane is to act as a barrier to keep the liquid / vapor interface at the pore entrance. Therefore, in the process of membrane distillation, in order to prevent the membrane from being wetted and causing functional failure, the membrane material must be hydrophobic, that is, it must have a high water contact angle; the second function of the membrane is to serve as a medium for the diffusion and heat insulation of water vapor, and the structure of the membrane should be porous. The pore size distribution, thickness, porosity, etc. of the membrane have a great influence on the permeation flux and retention rate of the membrane. In addition, considering the problem of long-term service, the membrane should have certain mechanical properties, chemical and thermal stability. The traditional membranes for membrane distillation mainly include flat-plate cast membranes prepared by phase inversion method and hollow fiber membranes prepared by wet spinning. However, low permeation flux and easy wetting of membrane pores and loss of retention effect are still the bottlenecks of membrane distillation technology, which limits its large-scale industrial application, mainly due to the insufficient hydrophobicity of the membrane surface, small pore size, low porosity and the structural characteristics of closed pores inside. The nanofiber porous membrane prepared by electrospinning technology has excellent structural characteristics, such as high porosity, interconnected open pore structure, and controllable pore size and membrane thickness, which can significantly improve the defect of low permeability flux of traditional membrane distillation membranes.
[0004] At present, commonly used MD membranes are usually polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polypropylene (PP) and polyethylene (PE). Among them, PVDF is a semi-crystalline polymer and a long-chain macromolecule at room temperature, with excellent chemical stability and excellent toughness, strong hydrophobicity, but poor pressure resistance; its copolymer polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP) is easily soluble in organic solvents, has a low melting point and is easy to prepare, has a low degree of crystallinity, and the tensile strength and elongation at break of PVDF-HFP membranes are significantly higher than those of PVDF membranes, making it a very promising material for preparing hydrophobic MD membranes. Ye Can et al. [Ye Can, Zhou Yue, Liu Fei, Wang Xiaozu, Wang Zhaohui, Cui Zhaoliang. Study on the alkali resistance of PVDF and its copolymer membranes [J]. Membrane Science and Technology, 2022, 42(01): 72-79.] prepared and compared the morphological characteristics, mechanical properties and chemical stability of PVDF membranes and PVDF copolymers (PVDF-HFP and PVDF-CTFE) membranes by electrospinning technology. The results showed that under the same membrane formulation and alkali solution treatment conditions, the mechanical properties and other properties of the prepared copolymer membranes were better than those of the homopolymer membranes, and the plasticity was better. In comprehensive comparison, PVDF-HFP nanofiber membranes had the best physical properties. With the further deepening of related research, Abdullah et al. [Ching-Iuan Su, Jyun-Han Shih, Meng -Shun Huang, Chih-Ming Wang, Wun-Ching Shih, Yen-sheng Liu. A Study of Hydrophobic Electrospun Membrane Applied in Seawater Desalination by Membrane Distillation [J]. Fibers and Polymers, 2012, 13 (6).] By adjusting the concentration of PVDF-HFP, PVDF-HFP nanofiber membrane was prepared by electrostatic spinning technology, and successfully applied to direct contact membrane distillation system. The study found that compared with PVDF composite nanofiber membrane, PVDF-HFP composite nanofiber membrane significantly improved permeation flux and retention rate in DCMD system. In addition, due to the presence of HFP group, the fluorine content is increased, the hydrophobic property is further improved, the membrane wetting phenomenon caused by the entry of water molecules is effectively blocked, and the membrane is not polluted by inorganic salts and organic matter to cause pore blockage, so that a relatively long-term moisture permeability can be maintained. Due to the limited separation performance of a single polymer membrane material, one or more functional additives can be introduced to mix with the membrane matrix to improve membrane performance and improve separation efficiency. Although many studies including the above have prepared nanofiber membranes related to PVDF-HFP, the permeation flux of pure PVDF-HFP membranes is still low and the mechanical properties are not excellent enough.
[0005] Compared with other conventional membrane preparation methods, the nanofiber membrane prepared by electrospinning has excellent porosity, controllable pore size distribution and fully interconnected pore structure. However, the preparation of nanofiber membrane by electrospinning technology will cause the membrane to face problems such as deterioration of mechanical stability while ensuring the high porosity of the membrane. Thermoplastic polyurethane (TPU) is a polymer with excellent mechanical properties and elastic modulus. It is composed of linear block copolymers, and its structure contains hard segments and soft segments. TPU has high mechanical strength, biocompatibility, elasticity and good wear resistance, which is conducive to the long-term operation of membrane distillation systems. There are both hydrophilic groups and hydrophobic groups on the TPU molecular chain segments, and the hydrophilic groups can provide more water vapor diffusion channels. Ge et al. [Jianfeng Ge, Yang Si, Fen FU, Jialin Wang, Jianmao Yang, Lingxiao Cui, BinDing, Jianyong Yu, Gang Sun. Amphiphobic fluorinated polyurethane composite microfibrous membranes with robust waterproof and breathable performances [J]. RSC Advances, 2013.] prepared PU / FPU nanofiber membranes by introducing fluorinated polyurethane (FPU) into TPU spinning solution based on electrospinning technology. The study showed that the addition of fluorinated materials increased the hydrophobic effect of TPU membrane to a certain extent; Liu Chunhui and his team [Liu Chunhui, Qian Xiaolei, Liao Xi. Design and development of polyurethane-based nanofiber composite fabrics and their waterproof and breathable properties [J]. International Textile Guide, 2021, 49(08): 26-33+41.] based on the research of Ge et al., PVB / PU / FPU nanofiber membranes were designed and prepared by electrospinning technology and hot pressing process. The results showed that the membrane not only had good mechanical properties and water vapor diffusion effect, but also had better hydrophobic properties. By electrospinning it together with PVDF-HFP, the hydrophilic groups in the membrane pores can be modified, reducing the mass transfer resistance and increasing the flux. The excellent hydrophobicity of the PVDF-HFP / TPU film finally obtained can effectively prevent liquid water from penetrating into the interior of the film, while water vapor in the form of water molecules can react with the hydrophilic groups modified in the membrane pores by hydrogen bonds and other effects, and continuously diffuse between the hydrophilic groups through the "adsorption-desorption" effect, thereby achieving water vapor permeation through "hygroscopic conduction". At the same time, the multi-level structure of the nanofiber membrane increases the pore size and porosity, reduces the mass transfer resistance, further improves the flux of the nanofiber membrane, and gives it good mechanical properties.
[0006] In view of the above problems, the present invention discloses a method for preparing a hydrophobic porous composite nanofiber membrane for distillation, which utilizes a method for co-spinning two polymers, polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP) and thermoplastic polyurethane (TPU), and introduces hydrophilic groups into the membrane pores to promote water vapor transfer, thereby constructing a nanofiber membrane for MD with high porosity, high permeation flux, high hydrophobicity and excellent mechanical properties. By adjusting the ratio of PVDF-HFP / TPU in the hydrophobic nanofiber membrane, the microscopic morphology, pore size distribution, wettability, thermal conductivity, mechanical properties and membrane distillation characteristics of the composite material are changed to further improve the comprehensive performance of the material, and it is expected to become a type of hydrophobic porous membrane material for membrane distillation with development potential in the fields of seawater desalination and brackish water purification. Summary of the invention
[0007] The invention provides a method for preparing a multi-level nanofiber composite membrane for membrane distillation. The multi-level nanofiber composite membrane is prepared by electrostatic spinning technology using polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP) and thermoplastic polyurethane (TPU) as raw materials for water treatment.
[0008] A method for preparing a multi-stage nanofiber composite membrane for membrane distillation comprises the following steps:
[0009] (1) adding PVDF-HFP powder to a mixed solvent of N,N-dimethylformamide (DMF) and acetone in a volume ratio of 3:1 to 2:1, and magnetically stirring at room temperature for 1 to 5 hours to obtain a 6 to 10 wt% PVDF-HFP solution;
[0010] (2) adding TPU particles to DMF solvent and magnetically stirring at room temperature for 3 to 9 hours to obtain a 6 to 10 wt % TPU solution;
[0011] (3) The PVDF-HFP solution and TPU solution prepared in the above steps (1) and (2) are mixed in a certain mass ratio, magnetically stirred at room temperature for 2 to 6 hours, and allowed to stand to remove bubbles for use, to obtain spinning solutions with different proportions and uniform dispersion; spinning is performed under electrospinning parameters (spinning voltage 25 to 40 kV, receiving distance 16 to 22 cm, spinning speed 0.2 to 2.0 mL / h, spinning environment temperature 15 to 30° C., relative humidity 25 to 40%) to obtain a primary PVDF-HFP / TPU multi-level nanofiber membrane;
[0012] (4) The nascent PVDF-HFP / TPU multi-level nanofiber membrane obtained in the above step (3) is vacuum dried at 45-75° C. for 20-30 hours to finally obtain a PVDF-HFP / TPU multi-level nanofiber membrane.
[0013] Preferably, the volume ratio of N,N-dimethylformamide (DMF) to acetone in step (1) is 5:2 to 2:1.
[0014] Preferably, the dissolution time in step (1) is 1 to 3 hours.
[0015] Preferably, the mass fraction of the PVDF-HFP solution in step (1) is 7 to 9 wt %.
[0016] Preferably, the dissolution time in step (2) is 5 to 7 hours.
[0017] Preferably, the mass fraction of the TPU solution in step (2) is 7 to 9 wt %.
[0018] Preferably, the stirring time in step (3) is 3 to 5 hours.
[0019] Preferably, the electrospinning parameters in step (3) are: spinning voltage 32-37 kV, receiving distance 17-20 cm, spinning speed 0.3-0.8 mL / h, spinning environment temperature 18-28° C., and relative humidity 30-40%.
[0020] Preferably, the vacuum drying temperature in step (4) is 55-65° C. and the time is 22-27 h.
[0021] Compared with the existing technology, the present invention has the following advantages and outstanding effects: (1) The PVDF-HFP membrane has strong hydrophobic properties, and its dense fiber structure increases its mass transfer resistance. By blending TPU to a certain extent, the porosity can be increased, the mass transfer resistance can be reduced, and the flux of membrane distillation can be increased; (2) There are both hydrophilic groups and hydrophobic groups on the TPU molecular chain segment, which has good waterproof and moisture permeability. The electrospinning technology is used to blend TPU and PVDF-HFP to prepare a multi-level structure hydrophobic nanofiber membrane. The hydrophilic groups are evenly distributed longitudinally inside the membrane, which can form a fast molecular channel, thereby reducing the mass transfer resistance and effectively improving the membrane flux; (3) TPU has excellent mechanical properties, wear resistance, and high elasticity, which effectively prolongs the service life of the membrane for membrane distillation. The present invention is expected to provide a new method for developing a new membrane for membrane distillation with excellent performance and long-term stability, and has broad application prospects in the fields of seawater desalination, high-salt wastewater and brackish water treatment. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The process flow chart of preparing multi-stage nanofiber composite membrane for membrane distillation;
[0023] Figure 2 This is an electron microscope image of a multi-stage nanofiber composite membrane for membrane distillation;
[0024] Figure 3This is a tensile fracture curve diagram of a multi-stage nanofiber composite membrane for membrane distillation;
[0025] Figure 4 This is a diagram of the membrane distillation performance of a multi-stage nanofiber composite membrane for membrane distillation. DETAILED DESCRIPTION
[0026] The present invention will be further described below in conjunction with specific embodiments.
[0027] Example 1
[0028] (1) Weigh an appropriate amount of PVDF-HFP powder and dissolve it in a mixed solvent of N,N-dimethylformamide (DMF) and acetone in a volume ratio of 7:3, and stir it magnetically at room temperature for 2 h to obtain a 8 wt% PVDF-HFP uniform transparent solution;
[0029] (2) Weighing an appropriate amount of TPU particles, adding them to DMF solvent, and magnetically stirring at room temperature for 6 h to obtain a 8 wt % TPU homogeneous transparent solution;
[0030] (3) The PVDF-HFP solution and TPU solution prepared in the above steps (1) and (2) were mixed in a mass ratio of 1:1, magnetically stirred at room temperature for 4 hours, and allowed to stand to remove bubbles to obtain spinning solutions with different ratios; spinning was performed under electrospinning parameters (spinning voltage 35 kV, receiving distance 18 cm, spinning speed 0.5 mL / h, spinning environment temperature 23±5°C, relative humidity 35±5%) to obtain a primary PVDF-HFP / TPU multi-level nanofiber membrane;
[0031] (4) vacuum drying the primary PVDF-HFP / TPU multi-level nanofiber membrane obtained in the above step (3) at 60° C. for 24 h to finally obtain a PVDF-HFP / TPU multi-level nanofiber membrane;
[0032] (5) Membrane distillation test: The membrane distillation performance of the prepared membrane was tested using a direct contact membrane distillation system consisting of a glass mold, an electronic balance, a conductivity meter, a peristaltic pump and a constant temperature water tank. The temperatures of the permeate and feed liquid were always maintained at 20°C and 60°C by a constant temperature water tank. Both the feed liquid and the permeate were circulated by a peristaltic pump with a constant flow rate of 0.5 L / min. The simulated seawater concentration was 3.5 wt% NaCl and the test area was 2×2 cm 2 The hydrophobicity of the membrane is characterized by measuring the water contact angle, the membrane flux is calculated by measuring the mass difference of the permeate solution, and the salt retention rate of the membrane is calculated based on the change in permeate conductivity. A 72-hour continuous DCMD test is used to investigate the long-term stability of the membrane during long-term operation. The permeate flux J is calculated by the weight change of the permeate solution and is calculated using the following formula:
[0033] J = ΔM / (ΔT×S)
[0034] Where: J is the flux (kg / m 2 h), ΔM permeate weight gain (kg), ΔT running time (h), S membrane effective area (cm 2 )
[0035] The salt rejection rate R is calculated by the conductivity of the permeate and is obtained by the following formula:
[0036] R=[(C f -C p ) / C f ]×100%
[0037] Where: R is the retention rate, C is the f Feed solution concentration (g / L), C p The concentration of the permeate (g / L). The solution concentration can be calculated from the conductivity based on the linear relationship between conductivity and concentration.
[0038] The prepared PVDF-HFP / TPU multi-level nanofiber composite membrane has good fiber morphology and uniform distribution, without fiber breakage, beading and bonding, and has an obvious multi-level structure. The average diameter of the fibers in the membrane is 237nm, the average pore size is 372.9nm, the porosity is above 88%, the surface roughness is 0.509, the contact angle is 123.7°, the fracture stress is 12.6Mpa, the fracture elongation is 105.4%, and the permeation flux is 28.58L / (m 2 h), the salt rejection rate is above 99.7%.
[0039] Example 2
[0040] (1) Same as Example 1;
[0041] (2) Same as Example 1;
[0042] (3) The PVDF-HFP solution and TPU solution prepared in the above steps (1) and (2) were mixed in a mass ratio of 2:1, magnetically stirred at room temperature for 4 hours, and allowed to stand to remove bubbles to obtain spinning solutions with different ratios; spinning was performed under electrospinning parameters (spinning voltage 35 kV, receiving distance 18 cm, spinning speed 0.5 mL / h, spinning environment temperature 23±5°C, relative humidity 35±5%) to obtain a primary PVDF-HFP / TPU multi-level nanofiber membrane;
[0043] (4) Same as Example 1;
[0044] (5) Same as Example 1;
[0045] The prepared PVDF-HFP / TPU multi-level nanofiber composite membrane has good fiber morphology and uniform distribution, without fiber breakage, beading and bonding, and has an obvious multi-level structure. The average diameter of the fibers in the membrane is 224nm, the average pore size is 354.7nm, the porosity is above 88%, the surface roughness is 0.752, the contact angle is 127.6°, the fracture stress is 9.8Mpa, the fracture elongation is 91.1%, and the permeation flux is 31.82L / (m 2 h), the salt rejection rate is as high as over 99.9%.
[0046] Example 3
[0047] (1) Same as Example 1;
[0048] (2) Same as Example 1;
[0049] (3) The PVDF-HFP solution and TPU solution prepared in the above steps (1) and (2) were mixed in a mass ratio of 3:1, magnetically stirred at room temperature for 4 hours, and allowed to stand to remove bubbles to obtain spinning solutions with different ratios; spinning was performed under electrospinning parameters (spinning voltage 35 kV, receiving distance 18 cm, spinning speed 0.5 mL / h, spinning environment temperature 23±5°C, relative humidity 35±5%) to obtain a primary PVDF-HFP / TPU multi-level nanofiber membrane;
[0050] (4) Same as Example 1;
[0051] (5) Same as Example 1;
[0052] The prepared PVDF-HFP / TPU multi-level nanofiber composite membrane has good fiber morphology and uniform distribution, without fiber breakage, beading and bonding, and has an obvious multi-level structure. The average diameter of the fibers in the membrane is 204nm, the average pore size is 342.3nm, the porosity is above 88%, the surface roughness is 0.719, the contact angle is 131.05°, the fracture stress is 8.1Mpa, the fracture elongation is 81.2%, and the permeation flux is 34.25L / (m 2 h), the salt rejection rate is as high as over 99.99%.
[0053] Example 4
[0054] (1) Same as Example 1;
[0055] (2) Same as Example 1;
[0056] (3) The PVDF-HFP solution and TPU solution prepared in the above steps (1) and (2) were mixed in a mass ratio of 4:1, magnetically stirred at room temperature for 4 hours, and allowed to stand to remove bubbles to obtain spinning solutions with different ratios; spinning was performed under electrospinning parameters (spinning voltage 35 kV, receiving distance 18 cm, spinning speed 0.5 mL / h, spinning environment temperature 23±5°C, relative humidity 35±5%) to obtain a primary PVDF-HFP / TPU multi-level nanofiber membrane;
[0057] (4) Same as Example 1;
[0058] (5) Same as Example 1;
[0059] The prepared PVDF-HFP / TPU multi-level nanofiber composite membrane has good fiber morphology and uniform distribution, without fiber breakage, beading and bonding, and has an obvious multi-level structure. The average diameter of the fibers in the membrane is 189nm, the average pore size is 302.5nm, the porosity is above 88%, the surface roughness is 0.921, the contact angle is 132.6°, the fracture stress is 7.5Mpa, the fracture elongation is 72.0%, and the permeation flux is 30.95L / (m 2 h), the salt rejection rate is as high as over 99.99%.
Claims
1. A method for preparing a multi-stage nanofiber composite membrane for membrane distillation, characterized in that: The following steps are involved: (1) Weigh a certain amount of PVDF-HFP powder and add it to a mixed solvent of DMF and acetone, and stir it evenly with a magnetic stirrer at room temperature to obtain a PVDF-HFP spinning solution; (2) Weighing a certain amount of TPU particles, adding them to DMF solvent, and stirring them evenly with a magnetic stirrer at room temperature to obtain TPU spinning solution; (3) The prepared PVDF-HFP spinning solution and TPU spinning solution are mixed in a certain mass ratio, magnetically stirred at room temperature until uniform, and allowed to stand to remove bubbles to obtain blended spinning solutions of different proportions; and a primary PVDF-HFP / TPU multi-level nanofiber composite membrane is prepared by electrospinning technology; (4) subjecting the primary PVDF-HFP / TPU multi-level nanofiber membrane to vacuum drying to obtain a PVDF-HFP / TPU multi-level nanofiber composite membrane; In the step (1), the volume ratio of DMF and acetone in the mixed solvent is 3:1 to 2:1, the dissolution temperature is room temperature, the dissolution time is 1 to 5 hours, and the mass fraction of the prepared PVDF-HFP spinning solution is 6 to 10 wt%; In the step (2), the dissolution temperature is room temperature, the dissolution time is 3 to 9 hours, and the mass fraction of the obtained TPU spinning solution is 6 to 10 wt%; In the step (3), the solvent mixing temperature is room temperature, the stirring time is 2 to 6 hours, and the electrospinning parameters are: spinning voltage 25 to 40 kV, receiving distance 16 to 22 cm, spinning speed 0.2 to 2.0 mL / h, spinning environment temperature 15 to 30° C., and relative humidity 25 to 40%; In the step (4), the vacuum drying temperature is 45 to 75° C. and the time is 20 to 30 hours; The fibers in the multi-level nanofiber composite membrane for membrane distillation have good morphology and are evenly distributed, without breakage, beading and bonding, and have a multi-level structure. The average fiber diameter ranges from 150 to 250 nm, the porosity of the fiber membrane is not less than 90%, the average pore size is 0.2 to 0.4 μm, the contact angle is 120° to 135°, and the elongation at break is 80 to 110%.